ADAS multi-sensor fusion system-based security and energy optimisation for an electric vehicle. (24th September 2019) - Cabani, Adnane; Khemmar, Redouane; Ertaud, Jean-Yves; Rossi, Romain; Savatier, Xavier
The works presented in this paper are a part of VIRTUOSE project which is dedicated to the development of an intelligent electric vehicle with range-extender and multiple energy sources. Our objective is to present ADAS multi-sensor fusion system which aims to optimise the energy consumption of an electric vehicle. Firstly, the system is limited just to advise the driver using estimated measurements like speed, power and/or the real data as limit speed. Secondly, in order to meet real-time and energy consumption constraints, which can be imposed by some kind of scenarios, the system will not only inform the driver for the speed to be adopted but also take full control of the vehicle if necessary. The platform is validated within not only simulation phases but also under indoor (vehicle test bench) and outdoor (real traffic) environment.